Strategic discipline: inconspicuous lessons from Germanic Mittelstand firms. Issue 4 (21st June 2019) - Lehrer, Mark; Schmid, Stefan
Abstract : Purpose: The purpose of this paper is to develop the hitherto unexplored concept of strategic discipline. Design/methodology/approach: Three fairly iconic firms of the Germanic Mittelstand (ALDI, Stihl and Hipp) are examined. The meaning and relevance of strategic discipline is derived. Findings: Intuitively, strategic discipline may seem like the antipode to the much-discussed concept of pivoting. In fact, strategic discipline is shown to be the natural corollary of strategic pivoting as a successive phase in a company's development. Research limitations/implications: In fast-moving or fast-changing environments, strategic discipline may be inappropriate. Furthermore, the exercise of strategic discipline can restrain growth. Once firms have attained a certain size and saturation of the market, the desire for further growth may entail a willingness to loosen the hold of strategic discipline. Practical implications: Strategic discipline can enable firms to avoid falling into common strategic pitfalls. From this paper, the authors distill three basic dimensions of strategic discipline: cultivating simplicity, resisting short-term temptations and focusing on implementability. Originality/value: The success of firms depends as much on the strategic choices they make as upon the strategic choices they decide not to make. Most prior research has focused on the visible strategy choices companies have made a lot more than on the practically invisible history of strategic choices that firms have not made. This contribution does the opposite, filling an evident gap.